Fundamentals of media effects - Bryant, Jennings, 1944-; Thompson, Susan, 1957-; Finklea, Bruce W., ....- (Long Grove (Ill.) : Waveland Press, 2013)
Mass media's potential to influence audience beliefs and behavior is a subject that has long fascinated scholars and the general public. The ongoing interest and concern are reflected in the common tendency to blame "the media" for many of society's problems. This extensively revised and updated edition cuts through popular notions of presumed effects to provide a balanced, informed, up-to-date treatment of the media effects literature. The clear, compelling presentation, illuminated by dozens of new photographs, equips readers with a fundamental understanding of the history, theoretical underpinnings, and current status of media effects research knowledge that will help them navigate in a media-saturated environment. Several outstanding elements distinguish the Second Edition of Fundamentals of Media Effects. New chapters explore the impact of computer/video games, the effects of the Internet and social networking sites, and the way mobile communication devices have transformed the way we live. An extensive new chapter on children's educational television describes the considerable body of research that supports positive effects like language development and flexible-thinking skills. Framing studies are covered in a separate chapter where they are distinguished both theoretically and experimentally from agenda setting and priming. Finally, the authors provide overviews of classic and current research studies in an invaluable feature called "Research Spotlight," which enable readers to envision how theories translate into research.
Previously published: Fundamentals of media effects / Jennings Bryant, Susan Thompson. Boston, Mass. : McGraw-Hill, c2002.
Includes bibliographical references (pages 323-392) and index.
Keywords: Mass communication; Mass media -- Influence -- United States; Mass media -- Political aspects -- United States; Mass media -- Psychological aspects -- United States; Mass media -- Social aspects -- United States; Mass media; Media effecten